De novo transcriptome analysis of Dysoxylum binectariferum to unravel the biosynthesis of pharmaceutically relevant specialized metabolites - Kumara, Patel Mohana; Varun, Eranna; Sanjay, Joshi Renuka; Madhushree, Anchedoddi Hanumegowda; Thimmappa, Ramesha (Frontiers in Plant Science, 2023)
The tropical tree, D. binectariferum, is a prominent source of chromone alkaloid rohitukine, which is used in the semi-syntheses of anticancer molecules such as flavopiridol and P-276-00. The biosynthetic pathway of rohitukine or its derivatives is currently unknown in plants.Here, we explored chromone alkaloid biosynthesis in D. binectariferum through targeted transcriptome sequencing. Illumina sequencing of leaves and roots of a year-old D. binectariferum seedling generated, 42.43 and 38.74 million paired-end short reads, respectively. Quality filtering and de novo assembly of the transcriptome generated 274,970 contigs and 126,788 unigenes with an N50 contig length of 1560 bp. The assembly generated 117,619 translated unigene protein sequences and 51,598 non-redundant sequences. Nearly 80% of these non-redundant sequences were annotated to publicly available protein and nucleotide databases, suggesting the completeness and effectiveness of the transcriptome assembly. Using the assembly, we identified a chalcone synthase (CHS) and three type III polyketide synthases (PKS-III; non-CHS type) that are likely to be involved in the biosynthesis of chromone ring/noreugenin moiety of rohitukine. We also identified key enzymes like lysine decarboxylase in the piperidine pathway that make the piperidine moiety of rohitukine. Besides these, the upstream enzymes in flavonoid biosynthesis like phenylalanine ammonia-lyase (PAL), trans-cinnamate 4-hydroxylase (C4H),4-coumarate-CoA ligase (4CL), and chalcone isomerase (CHI) have also been identified. Also, terpene synthases that are likely to be involved in the biosynthesis of various terpenoid scaffolds have been identified. Together, the D. binectariferum transcriptome resource forms a basis for further exploration of biosynthetic pathways of these valuable compounds through functional validation of the candidate genes and metabolic engineering in heterologous hosts. Additionally, the transcriptome dataset generated will serve as an important resource for research on functional genomics and enzyme discovery in D. binectariferum and comparative analysis with other Meliaceae family members.